MARKETING MIX IN THE CONSUMER VIEW AND CONFIDENCE THAT AFFECT THE DECISION TO BUY PRECAST CONCRETE WALL HOUSE IN BANGKOK AND PERIMETER - Thongkam, Pongsak; Chemasangkanan, Suwat; Rittiboonchai, Wisit (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2021)
The purposes of the study research were: 1) to study to the individual factors when making decisions to buy precast concrete wall houses, and 2) to study the marketing mix from the consumer view and the effects of the confidence level on such decisions. The study was a quantitative research with the samples of 401 people. The research tool was a questionnaire. The statistics for data analysis used were frequency, percentage, mean, and standard deviation. The statistics for hypothesis test were t-test, One-way ANOVA, and multiple regression analysis. The research results show that: 1) There are statistically significant differences in age, occupation and monthly income to buying decision in a residential house, precast concrete wall system of the housing estate project. 2) Marketing mix factor (X1) and brand confidence factor (X3) have a statistically significant influence on prefabricated concrete wall purchase decision. Accordingly, the equations can contribute to 53 percent of the forecast. The equation can be written as Ytot = 0.31 + 0.32 (X1) + 0.52 (X3).